PERUBAHAN DESAIN RUMAH TINGGAL JAWA MENJADI RUANG PUBLIK TERBATAS (Dari Rumah Bangsawan ke Hunian Publik) - Wardani, Laksmi Kusuma (Institute of Research and Community Outreach - Petra Christian University, 2007)
A house or dalem Joyokusuman, is treated as a big mountain where life resources are obtained by its inhabitants, experiencing transition due to the encouragement of human knowledge, travelling from a simple to a more complex level. A significant change occurred in the function of central senthong, which initially functioned as a place of contemplation, the integration of The Absolute One of the Universe (Brahma) with the Self, but has now become a circulation space. A change has also occured in the nature of space that was initially private, and has now become limitedly public. The continuous circulation flow has changed to all directions, causing impacts in the circulation between inhabitants, guests and servants in the palace due to the variety of entrepreneurial activities. The transition of function, space nature and fulfillment of activity facilities in the space has made its interior setting overloaded. Besides that, due to the existing business activities, the space has become more open for public. The vast feeling of space becomes reduced because of the presence of overload furniture, however, it is neutralized by the open form of space maintaining its natural atmosphere. These transitions prominently show that the once sacred space of dalem has now become profane because of business activities. Abstract in Bahasa Indonesia : Rumah atau dalem Joyokusuman, diperlakukan sebagai gunung besar yang menjadi sumber kehidupan penghuninya, mengalami perubahan sebagai akibat dorongan pengetahuan manusia. Perubahan yang signifikan terjadi pada fungsi senthong tengah, yakni awalnya sebagai tempat kontemplasi, manunggalnya Semesta Tunggal Absolut (Brahma) dengan si Diri, saat ini berubah fungsi sebagai ruang sirkulasi. Perubahan terjadi pula pada sifat ruang yang dahulu privat, berubah menjadi publik terbatas. Alur sirkulasi yang menerus berubah ke segala arah, terjadi tabrakan sirkulasi antara penghuni, tamu maupun abdi dalem sebagai akibat beragamnya aktivitas usaha. Perubahan fungsi, sifat ruang, sirkulasi, dan pemenuhan fasilitas kegiatan dalam ruang membuat penataan interior menjadi berlebihan. Akibat adanya aktivitas usaha, membuat ruang menjadi lebih terbuka untuk publik. Kesan luas ruang menjadi berkurang karena furnitur yang berlebihan, namun masih dapat dinetralisir dengan bentuk ruang yang terbuka, sehingga kesan alami masih terjaga. Perubahan tersebut di atas menunjuk dengan jelas bahwa dalem yang dulunya sakral berubah menjadi propan karena aktivitas usaha. Kata kunci: Perubahan, Rumah Jawa, Ruang Publik